Non-genetic mechanisms in cancer evolution: senescence, unicellularization, and cycles of stemness recovery - Vladimir F. Niculescu (Academia Molecular Biology and Genomics)
All germlines—including those of humans, protists, cancer, and metazoans—are capable of proliferating through asymmetric cell division, giving rise to committed stem cells. Their common evolutionarily roots trace back to the hypoxic germline of the last common ancestor of amoebozoans, metazoans, and fungi, referred to as the Ur-germline. Consequently, all modern germlines that produce stem cells—including the cancer stemgermline—retain physiological characteristics of this ancestral Ur-germline. Stress, particularly hyperoxic germline conditions, can irreversibly damage the DNA repair genes in the stemgermline, leading to genome dysfunction, mitotic arrest (senescence), and loss of key functions such as stemness and asymmetric cell division. In most cases, genomically compromised senescent cells in humans and animals undergo apoptotic senescence and are eliminated. However, a minority of dysfunctional cells undergo restorative senescence, initiating a process of unicellularization and genome reconstruction. During unicellularization, genes associated with multicellular functions are downregulated, while ancient unicellular stemgermline genes are upregulated. Cells exiting restorative senescence follow a genome repair program via characteristic unicellular mechanisms, such as hyperpolyploidization and depolyploidization. This process gives rise to progenitor cells that establish a cancer stemgermline and a unicellular cancer cell system. Briefly, restorative senescence escapers restore genomic architecture, function, and molecular integrity using evolutionary mechanisms inherited from the Ur-germline.